Influência da estimulação aversiva visual na atenção concentrada e na memória de curto prazo em estudantes universitários - Giron,Paulo Ricardo de Oliveira (Universidade do Vale do Rio do Sinos, 2009)
This work presents a bibliographical review of material from Web of Science database. 266 publications were found that link directly aversive stimulation and cognition. Based on further analysis, 53 studies were used for this review. It was made a citation of the main categories and methods then, as well as topics that address the current researches and main progresses on the theme. Considering the selected papers, although there is considerable progress, mainly, in the last two decades on this topic, it is still a field that needs a lot of study in order to evaluate the interference of cognition by aversive stimulation.
Keywords: emoção; funções cognitivas; estímulo; cognitive functions; emotion; stimuli; Ciências Humanas